Proper Islamic consumption shopping among the Malays in modern Malaysia - Fischer, Johan (Nordic Institute of Asian Studies monograph series, 2008)
Similar to the Western organic movement, a halal movement is spreading in the Muslim world. Exploring consumption practices in urban Malaysia, this book shows how diverse forms of Malay middle-class consumption are understood, practised and contested. It also traces linkages between class, consumption, market relations, Islam and the state